2019
DOI: 10.1063/1.5100600
|View full text |Cite
|
Sign up to set email alerts
|

Deeply supercooled aqueous LiCl solution studied by frequency-resolved shear rheology

Abstract: To characterize the structural relaxation of an aqueous solution of LiCl, frequency-dependent shear rheological experiments are carried out near its glass transition. Analyzed within the fluidity representation, the generic spectral shape that was previously found for a range of different kinds of glass formers is confirmed for the currently studied hydrogen-bonded fluid as well. Furthermore, the validity of the rheological equivalent of the Barton-Nakajima-Namikawa relation is demonstrated for the aqueous LiC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 146 publications
1
14
0
Order By: Relevance
“…13, it was shown that the dielectric response of ethaline cannot be fitted by the RBM alone, 46 while for several other glass formers, this approach was found to be applicable. 55 As discussed in Sec. I, the RBM was not conceived to describe spectra FIG.…”
Section: A Dielectric Spectramentioning
confidence: 97%
See 2 more Smart Citations
“…13, it was shown that the dielectric response of ethaline cannot be fitted by the RBM alone, 46 while for several other glass formers, this approach was found to be applicable. 55 As discussed in Sec. I, the RBM was not conceived to describe spectra FIG.…”
Section: A Dielectric Spectramentioning
confidence: 97%
“…We ascribe these to spurious contributions in J ′ (ν) due to the low-torque limitations of the rheometer. 48,49,55,61 To a lesser extent, they also affect the glyceline spectra [cf. the two highest temperatures in Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting possibility is the relaxation-like process, sometimes assumed to universally occur in dielectric permittivity spectra due to ionic diffusion. 60,61,62,63,64 A prominent example is a small relaxation process found in ' measurements of the ionic-melt glass former [Ca(NO 3 ) 2 ] 0.4 [KNO 3 ] 0.6 (CKN), which does not contain any dipolar molecules or ions. 60,65 Within the modulus fomalism for the description of ionic conductors, its occurrence is rationalized by a distribution of conductivity-relaxation times.…”
Section: B Dielectric Spectramentioning
confidence: 99%
“…16,17 The former two electrolytes behave as "simple" liquids, the latter two display clear evidence of chain dynamics at frequencies below wa. The type V materials are linear polymers with different chain lengths, 18,19 whereas a water solution of lithium chloride 21 is considered as type VIcorresponding to aqueous systems.…”
mentioning
confidence: 99%